Extrinsic allergic bronchiolitis in a bird fancier. Issue 2 (May 1984) - Harries, M G; Heard, B; Geddes, D
Abstract : A patient in whom a severe systemic illness was characterised by weight loss, arthralgia and breathlessness was exposed to her pet bird. This pragmatic approach reproduced the features of her illness. The changes that occurred in her pulmonary physiology and histology differed from those seen in extrinsic allergic alveolitis in many important respects.